Regulation of Oncogenic Targets by Tumor-Suppressive miR-150-3p in Lung Squamous Cell Carcinoma - Mizuno, Keiko; Tanigawa, Kengo; Misono, Shunsuke; Suetsugu, Takayuki; Sanada, Hiroki; Uchida, Akifumi; Kawano, Minami; Machida, Kentaro; Asai, Shunichi; Moriya, Shogo; Inoue, Hiromasa; Seki, Naohiko (Biomedicines, 2021)
Several recent studies have shown that both strands of certain miRNAs derived from miRNA duplexes are involved in cancer pathogenesis. Our own recent studies revealed that both strands of the miR-150 duplex act as tumor-suppressive miRNAs in lung adenocarcinoma (LUAD) through the targeting of several oncogenes. The aim of the study here was to further investigate the tumor-suppressive roles of miR-150-3p (the passenger strand) in lung squamous cell carcinoma (LUSQ) and its control of cancer-promoting genes in LUSQ cells. The downregulation of miR-150-3p in LUSQ tissues was confirmed by data in The Cancer Genome Atlas (TCGA). The ectopic expression of miR-150-3p attenuated cancer cell aggressive features, e.g., cell cycle arrest, migration and invasive abilities. Our target search strategy successfully identified a total of 49 putative targets that were listed as subjects of miR-150-3p regulation in LUSQ cells. Interestingly, among these targets, 17 genes were categorized as related to the “cell cycle” based on Gene Ontology (GO) classification, namely CENPA, CIT, CCNE1, CCNE2, TIMELESS, BUB1, MCM4, HELLS, SKA3, CDCA2, FANCD2, NUF2, E2F2, SUV39H2, CASC5, ZWILCH and CKAP2). Moreover, we show that the expression of HELLS (helicase, lymphoid specific) is directly controlled by miR-150-3p, and its expression promotes the malignant phenotype of LUSQ cells.